Sosialisasi Pemberian ASI Eksklusif dan MPASI yang Tepat sebagai Upaya Pencegahan Stunting pada Anak Balita - Aisy, Nisrina Rihadatul; Dini, Syawla Eka; Hanifah, Lulu Fajri; Mahbuby, Dwiki Arif Nabil; Anjani, Laila (Yayasan Daarul Huda Kruengmane, 2024)
Stunting in toddlers is a serious health problem in Indonesia, with a prevalence reaching 24.4% in 2021. Inadequate nutrition, especially in the first 1000 days of life, is the main factor causing stunting. This community service aims to improve mothers' understanding of the importance of providing exclusive breastfeeding and appropriate complementary foods (MPASI) as an effort to prevent stunting. The socialization activity was carried out in Rajeg Village, Rajeg District, Tangerang Regency, involving 50 participants consisting of mothers with toddlers and pregnant women. The methods used included pre-test, material, socialization, educational games, and post-test. The results showed a significant increase in understanding from 30% to 85% after participating in the program. Educational games proved effective in strengthening participants' understanding, with 95% reporting that this method was very helpful. As many as 80% of participants stated an increase in confidence in providing breast milk and MPASI, while 70% were committed to becoming agents of change in their environment. Challenges faced included difficulty understanding medical terms and the need for practical sessions on making MPASI. This activity successfully increased public awareness about the importance of Exclusive Breastfeeding and proper MPASI, with 85% of participants willing to participate in follow-up activities and monitoring. It is hoped that this increase in knowledge can contribute to reducing stunting rates in the area in the long term.